Surface integrity of Inconel 718 under cryogenic and dry cutting conditions - Muammar Faiq Azhar,; Che Hassan Che Haron,; Jaharah Abdul Ghani,; Nurul Hayati Abdul Halim, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Inconel 718 is a nickel-based alloy that has been developed with superior mechanical strength, creep resistance, and corrosion, as well as erosion resistance at temperatures above 649 ˚C. It is suitable to be used for aircraft engine components such as turbine discs. However, it also has low heat conductivity and the presence of hard carbide particles in its alloy worsens the machining conditions with high cutting temperature, and high shear force and promotes work hardening. Thus, this study aims to evaluate the surface integrity of Inconel 718 in terms of surface roughness, plastic deformation, and micro-hardness alterations after the turning process. Cryogenic CO2 cooling was supplied along the cutting process to reduce cutting temperatures and the machining performances were compared with dry machining. The experimental works show that the dry machining resulted in lower surface roughness by up to 42.15% as compared to cryogenic. However, the depth of plastic deformation under dry machining was much more severe than in cryogenic machining driven by higher cutting temperatures and pressure from the worn tool. The depth of plastic deformation became more distinct as the cutting speed increased. While the microhardness alteration of the machined surface was higher under cryogenic machining due to extensive cooling capacity by the CO2 flow. Thus, this study reveals that cryogenic cooling during metal cutting can produce products that have better wear resistance as well as higher surface hardness.